Hormonal Contraceptives and the Risk of Venous Thrombosis - Khialani, Deeksha; Rosendaal, Frits; Vlieg, Astrid van Hylckama (Seminars in Thrombosis and Hemostasis, 2020)
The risk of venous thrombosis (VT) varies according to the type of progestogen that is found in combined oral contraceptives (COCs). When combined with the estrogen component ethinylestradiol (EE), the androgenic progestogens are better able to counteract the EE-induced stimulation of liver proteins and hence are associated with a twofold decreased risk of VT compared with non- or antiandrogenic progestogens, which exert limited counteraction of EE. Because EE is responsible for the increased risk, novel estrogens such as estradiol were developed and seem to have a lower risk of VT than EE. Besides COCs, there are other methods of hormonal contraceptives, such as progestogen-only contraceptives, which do not increase VT risk, except for injectables. Other nonoral contraceptives are combined vaginal rings and patches. There is insufficient evidence regarding the risk of VT associated with these two methods compared with COCs. The increased risk associated with COCs is more pronounced in women with inherited thrombophilia. In these women, the progestogen levonorgestrel seems to be associated with the lowest risk of VT. Currently, there are no studies that have investigated the risk of VT in women who switch COCs. We hypothesize that switching COCs, even when switching from a high- to a low-risk COC, increases the risk of VT. Finally, risk prediction models in women who use COCs are lacking. Since there is a large number of VT cases associated with COC use, it is important to identify women at risk of VT and advise them on alternative contraception methods.
Keywords: contraceptives; oral; combined oral contraceptives; thrombosis; risk